2021
DOI: 10.1007/s00421-021-04680-x
|View full text |Cite
|
Sign up to set email alerts
|

Anti-carcinogenic effects of exercise-conditioned human serum: evidence, relevance and opportunities

Abstract: Regular physical activity reduces the risk of several site-specific cancers in humans and suppresses tumour growth in animal models. The mechanisms through which exercise reduces tumour growth remain incompletely understood, but an intriguing and accumulating body of evidence suggests that the incubation of cancer cells with post-exercise serum can have powerful effects on key hallmarks of cancer cell behaviour in vitro. This suggests that exercise can impact tumour biology through direct changes in circulatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 107 publications
1
19
0
Order By: Relevance
“…The plasma collected from highly conditioned young men, but not from low-PF individuals, decreased the PC3 cell viability and lowered cell proliferation. These results are in line with the results previously reported by a series of systematic reviews and meta-analysis recently published, which demonstrated the anticarcinogenic potential of peripheral blood factors of exercised individuals ( Metcalfe et al, 2021 ; Soares et al, 2021 ). The regular practice of exercise leads to chronic adaptations that reduce cancer risk through changes in cancer risk circulating biomarkers ( Friedenreich et al, 2017 ).…”
Section: Discussionsupporting
confidence: 93%
“…The plasma collected from highly conditioned young men, but not from low-PF individuals, decreased the PC3 cell viability and lowered cell proliferation. These results are in line with the results previously reported by a series of systematic reviews and meta-analysis recently published, which demonstrated the anticarcinogenic potential of peripheral blood factors of exercised individuals ( Metcalfe et al, 2021 ; Soares et al, 2021 ). The regular practice of exercise leads to chronic adaptations that reduce cancer risk through changes in cancer risk circulating biomarkers ( Friedenreich et al, 2017 ).…”
Section: Discussionsupporting
confidence: 93%
“…Regular release of muscle-derived anti-inflammatory cytokines (IL-6, IL-7, IL-10, IL-15), linked with the inhibition of pro-inflammatory cytokines (IL-1β, IL-18, TNF-α), have been purported to play important roles in the beneficial effects of exercise on immunity [75,78,79]. Indeed, there is growing evidence suggesting an anti-carcinogenic effect of exercise through direct changes in circulating proteins, RNA molecules and metabolites [80].…”
Section: Exercise Is Beneficial For Immunological Healthmentioning
confidence: 99%
“…Early preclinical evidence shows that the systemic responses to exercise can regulate cancer cell proliferation in vitro 15,16 . Indeed, our recent meta‐analysis demonstrated that stimulating a range of cancer cell lines with human serum obtained immediately after exercise reduces cell proliferation by ≈9% 17 .…”
Section: Introductionmentioning
confidence: 99%